The Scandinavian Regional Model:: Accounting for the shift from convergence to divergence - Torfing, Jacob; Lidström, Anders; Røiseland, Asbjørn (Scandinavian Journal of Public Administration, 2015)
This article maps how the sub-national regional levels of governance in Denmark, Norway and Sweden have changed from a high degree of institutional convergence to a pattern of institutional divergence. It analyses the similarities and differences in the changes in regional governance and discusses how these changes can be understood. Our supposition is that the more or less rational explanations of change found in main strands of the new institutionalism fail to explain the recent reforms of regional governance. Consequently, we ourselves have to contend with explanations in which rational action plays a limited role and contingent articulations of political and institutional conditions, together with spillover effects from reforms of local governance structures, are central to understanding the reforms that have produced the increasingly divergent patterns of regional governance in Scandinavia.